Deciphering sources of U contamination using isotope ratio signatures in the Loire River sediments: Exploring the relevance of 233U/236U and stable Pb isotope ratios. (November 2022) - Morereau, Amandine; Jaegler, Hugo; Hain, Karin; Steier, Peter; Golser, Robin; Beaumais, Aurélien; Lepage, Hugo; Eyrolle, Frédérique; Grosbois, Cécile; Cazala, Charlotte; Gourgiotis, Alkiviadis
Abstract: A broad range of contaminants has been recorded in sediments of the Loire River over the last century. Among a variety of anthropogenic activities of this nuclearized watershed, extraction of uranium and associated activities during more than 50 years as well as operation of several nuclear power plants led to industrial discharges, which could persist for decades in sedimentary archives of the Loire River. Highlighting and identifying the origin of radionuclides that transited during the last decades and were recorded in the sediments is challenging due to i) the low concentrations which are often close or below the detection limits of routine environmental surveys and ii) the mixing of different sources. The determination of the sources of anthropogenic radioactivity was performed using multi-isotopic fingerprints ( 236 U/ 238 U, 206 Pb/ 207 Pb and 208 Pb/ 207 Pb) and the newly developed 233 U/ 236 U tracer. For the first time 233 U/ 236 U data in a well-dated river sediment core in the French river Loire are reported here. Results highlight potential sources of contamination among which a clear signature of anthropogenic inputs related to two accidents of a former NUGG NPP that occurred in 1969 and 1980. The 233 U and 236 U isotopes were measured by recent high performance analytical methods due to their ultra-trace levels in the samples and show a negligible radiological impact on health and on the environment. The determination of mining activities by the use of stable Pb isotopes is still challenging probably owing to the limited dissemination of the Pb-bearing material marked by the U-ore signature downstream to the former U mines. Graphical abstract: Image 1 Highlights: First results of 236 U and 233 U in a sediment core collected in the Loire River. 236 U source contribution was deciphered using 233 U/ 236 U atomic ratio. Stable lead isotopes were used to discriminate past uranium mining activities. Lead isotopes showed only the influence of gasoline lead.